Determination of Homopolymerization Kinetics of 10‐(N‐Methylacrylamido)‐decylphosphonic acid, Its Diethyl ester, and 10‐(Methacryloyloxy)‐decylphosphonic acid, and Their Copolymerization with Methyl methacrylate. Issue 24 (24th November 2015) - Chmela, Štefan; Pavlinec, Juraj; Fiedlerová, Agnesa; Catel, Yohann; Moszner, Norbert
Abstract : Two polymerizable phosphonic acids destined to be constituents of self‐etch adhesives as well as a diethyl phosphonate bearing an N ‐methylacrylamide group are examined for their polymerization and copolymerization activity in methanol between 45 and 65 °C. Polymerization proceeds readily through a thermal free radical initiator. The intensity exponents for the monomer and initiator are only slightly over 1 and ≈0.5, respectively, in accordance with the results typically observed for an ideal free radical polymerization with bimolecular termination. The specific feature of this process is the absence of auto‐acceleration during the phosphonic acid monomer polymerization and polymer network formation in case of the phosphonate monomer. The kinetics of copolymerization with methyl methacrylate (MMA) are monitored by online 1 H NMR spectroscopy. Two copolymerization reactions for each pair of comonomers are sufficient to evaluate the kinetic data using the Jaacks method, the Fineman–Ross method, and the nonlinear least squares method. All three methods give similar results for particular monomer/MMA couples. Abstract : Homopolymerization of N ‐alkylacrylamides M1 and M2 as well as methacrylate M3 is performed in MeOH using azobisisobutyronitrile as an initiator. MonomerM2 is the most reactive. The copolymerization ofM1, M2, andM3 with methyl methacrylate (MMA) is studied. AlthoughM3 and MMA exhibit similar reactivities, monomersM1 andM2 polymerize much slower than MMA.